2022
DOI: 10.20517/ss.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Reliable metal alloy contact for Mg3+δBi1.5Sb0.5 thermoelectric devices

Abstract: Proper contacts between thermoelectric (TE) materials and electrodes are critical for TE power generation or refrigeration. The Bi-rich n-type Zintl material Mg3+δBi2-xSbx exhibits very good TE performance near room temperature, which makes Mg3+δBi2-xSbx-based compounds highly promising candidates to replace the Bi2Te3-ySey alloys, but ideal contacts that can match their TE performance have not yet been well studied. Here we investigate different metal (Ni and Fe) and metal alloy (NiFe, NiCr, NiCrFe, and stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…optimizing TEcMs 10,38 , designing TEiMs 29,[34][35][36]58 , and applying protective coating 28,58 . Typically, He et al successfully fabricated reliable TE devices by higher temperature sintering and Mg heavy overcompensation, and the robust modules are proved via thermal shock testing over 30,000 times when T h varied between 50 and 227 °C 38 .…”
Section: Progress In Mg 3 Sb 2 -Based Te Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…optimizing TEcMs 10,38 , designing TEiMs 29,[34][35][36]58 , and applying protective coating 28,58 . Typically, He et al successfully fabricated reliable TE devices by higher temperature sintering and Mg heavy overcompensation, and the robust modules are proved via thermal shock testing over 30,000 times when T h varied between 50 and 227 °C 38 .…”
Section: Progress In Mg 3 Sb 2 -Based Te Devicesmentioning
confidence: 99%
“…assembling 24,25 . As a result, there is still a yawning gap between theoretical and experimental conversion efficiency (η), and output power density (ω) for the reported Mg 3 Sb 2 -based TE devices [18][19][20][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Some alloying TEiM layers for n‐type Mg 3 Sb 1‐ x Bi x TEcM legs, including 304 stainless steel (304SS), [ 36 ] Mg 2 Cu, [ 10 ] Fe 90 Sb 10 , [ 37 ] and Mg 3.4 Sb 3 Ni [ 38 ] were subsequently reported to show lower ρ c values. Very recently, Song et al reported that the NiFe/Mg 3 Bi 1.5 Sb 0.5 contact exhibits a highly stable ρ c of 13 µΩ cm 2 after aging for over 2100 h. [ 39 ] The authors have suggested an alloying approach to design the TEiM rather than using available alloys, which has already been verified as an effective technique route with some necessary characteristics, including high bonding propensity, coefficient of thermal expansion (CTE) matching, diffusion passivation, and dopant inactivation. [ 25 ] For example, in our previous work, we selected Fe from 15 elements as the matrix element, considering the criteria of high σ s and low ρ c , and further designed two ternary alloys (Fe 7 Mg 2 Cr and Fe 7 Mg 2 Ti) with σ s > 40 MPa and ρ c < 5 µΩ cm 2 according to the above principles.…”
Section: Introductionmentioning
confidence: 99%